Superconductivity at Interfaces in Cuprate‐Manganite Superlattices - Nicolas Bonmassar; Georg Christiani; Tobias Heil; Gennady Logvenov; Y. Eren Suyolcu; Peter A. van Aken (Advanced Science, 2023)
Abstract One of the unsolved problems for using high‐Tc superconducting cuprates for spintronic applications are the short coherence lengths of Cooper pairs in oxides (a few Å), which requires atomically sharp and defect‐free interfaces. This research demonstrates the presence of high‐Tc superconducting La1.84Sr0.16CuO4 in direct proximity to SrLaMnO4 and provides evidence for the sharpness of interfaces between the cuprate and the manganite layers at the atomic scale. These findings shed light on the impact of the chemical potential at the interface of distinct materials on highly sensitive physical properties, such as superconductivity. Additionally, this results show the high stability of ultrathin layers from the same K2NiF4‐type family, specifically one unit cell of Sr2−xLaxMnO4 and three unit cells of La1.84Sr0.16CuO4. This work advances both the fundamental understanding of the proximity region between superconducting cuprates and manganite phases and the potential use of oxide‐based materials in quantum computing.